Alternative transmission modes for Trypanosoma cruzi - Christopher M. Kribs-Zaleta (Mathematical Biosciences and Engineering)
The parasite Trypanosoma cruzi, which causes Chagas' disease, istypically transmitted through a cycle in which vectors become infectedthrough bloodmeals on infected hosts and then infect other hosts throughdefecation at the sites of subsequent feedings. The vectors nativeto the southeastern United States, however, are inefficient at transmitting T. cruzi in this way, which suggests that alternative transmissionmodes may be responsible for maintaining the established sylvatic infectioncycle. Vertical and oral transmission of sylvatic hosts, as well asdifferential behavior of infected vectors, have been observed anecdotally.This study develops a model which accounts for these alternative modes oftransmission, and applies it to transmission between raccoons and the vector Triatoma sanguisuga. Analysis of the system of nonlinear differentialequations focuses on endemic prevalence levels and on the infection's basicreproductive number, whose form may account for how a combination oftraditionally secondary infection routes can maintain the transmission cyclewhen the usual primary route becomes ineffective.